Analysis of Emergency Planning Zones in Relation to Probabilistic Risk Assessment and Economic Optimization for International Reactor Innovative and Secure - Alzbutas, Robertas; Norvaisa, Egidijus; Maioli, Andrea (IntechOpen, 2012)
None